Estimation of Antibodies against Saccharomyces Cerevisiae in Patients with Indeterminate Colitis - Mahdi, Batool M. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Indeterminate colitis (IC) originally referred to those 10–15% of cases of inflammatory bowel disease (IBD) in which there was difficulty distinguishing between ulcerative colitis (UC) and Crohn’s disease (CD) in the colectomy specimen and histopathology examination. However, IC is increasingly used when a definitive diagnosis of UC or CD cannot be made at colonoscopy examination, colonic biopsies or at colectomy. The diagnostic difficulties may explain the variably reported prevalence of IC. Clinically, most patients with IC evolve to a definite diagnosis of UC or CD on follow up. Patients and methods: PATIENTS GROUP: Consisted of 80 patients with indeterminate colitis (IC), their age ranged (16-84 years), mean age was 45.5 years, 50 (62.5%) were males and 30 (37.5%) were females. CONTROL GROUP: Consist of 40 healthy volunteers, mean age was 39.3 years, 20 of them were male and the rest were females. Anti-Saccharomyces cerevisiae antibodies (ASCA) were detected using indirect immunofluorescence test (IIF) test. Results: Results of ASCA antibodies in the serum of IC patients showed significant higher frequency (66.2%)(p>0.001) than control group(7.5%). The commonest isotype of this ASCA antibody was IgG (53.7%) that is significantly higher than control group (P>0.001). The sensitivity of ASCA was 63.1 %, specificity was 28.5% and positive predictive value of ASCA was 80% and negative predictive value was 78.5%. Conclusions: In conclusion, higher frequency of ASCA (IgG) expression in IC was useful in early estimation of IC and could be used as serological marker.